2014
DOI: 10.2341/12-527-c
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effect of Casein Phosphopeptide–amorphous Calcium Phosphate on Postoperative Sensitivity Associated With In-office Vital Tooth Whitening

Abstract: Tooth sensitivity is the most frequent adverse effect of in-office vital tooth whitening. The use of a desensitizing gel after tooth whitening may reduce the incidence and severity of inoffice vital tooth-whitening sensitivity. SUMMARYThe aim of this study was to evaluate the efficacy of tooth mousse containing 10% casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) in reducing tooth sensitivity associated with in-office vital tooth whitening. In-office tooth whitening was performed for 51 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…In the present study, it was also possible to observe that TS was no longer reported four days after the bleaching sessions. Many clinical studies show that bleaching induced TS only occurs in a few days [19][20][21][76][77][78][79]. This finding can be explained by the process of lymphatic drainage of the pulp tissue, which is able to disperse toxic products that reach this connective tissue.…”
Section: Plos Onementioning
confidence: 99%
“…In the present study, it was also possible to observe that TS was no longer reported four days after the bleaching sessions. Many clinical studies show that bleaching induced TS only occurs in a few days [19][20][21][76][77][78][79]. This finding can be explained by the process of lymphatic drainage of the pulp tissue, which is able to disperse toxic products that reach this connective tissue.…”
Section: Plos Onementioning
confidence: 99%
“…7 In another study the mean dentin hypersensitivity was found to be 3.23 + 0.6 with fluoride varnish and 3.68 + 1.33 with CPP-ACP paste. 8 Navya Puvvula et al conducted a study to compare the effect of fluoride Varnish, Fluoride releasing composite, and CPP-ACP fluoride on demineralization around bracket. The author demonstrated that in GC tooth mousse group, the lesion depth was reduced by 67.4%.…”
Section: Resultsmentioning
confidence: 99%
“…7 In another study the mean dentin hypersensitivity was found to be 3.23 + 0.6 with fluoride varnish and 3.68 + 1.33 with CPP-ACP paste. 8 There is continuous debate between the dentists that which method is best for relieving the patient from pain. There are two studies conducted so far and both have variable results.…”
Section: Introductionmentioning
confidence: 99%
“…Casein phosphopeptide-amorphous calcium phosphate added to at-home whitening gels has shown a reduction in sensitivity (25). In a study comparing 10% CPP-ACP gel to a 2% sodium fluoride gel, a placebo found that the 10% CPP-ACP gel and the 2% sodium fluoride gel both reduced the sensitivity to a moderate level but were not different (26). Chewing gum is one of the most recent desensitizing treatments studied.…”
Section: Introductionmentioning
confidence: 96%